Reliability and Effectiveness of the Manchester Orbital Exenteration Wound Assessment Tool: Inter-Observer Agreement. (June 2015) - Cooper, John; Dharmasena, Aruna; Malik, Rizwan; Cook, Anne
ABSTRACT Aim: To evaluate the inter-observer agreement of the Manchester Orbital Exenteration Wound Assessment Tool (MOEWAT), a tool designed to facilitate grading of healing in exenterated sockets, scores from clinical photographs of exenterated sockets. Methods: Existing MOEWAT system was modified to allow grading of clinical photographs. Photographs of 36 different patients at different stages of healing following exenteration were identified. Scores for two masked observers, who independently graded the photographs were compared. The inter-observer agreement of scores was assessed using a Bland-Altman plot, with the average agreement and 95% confidence interval around the mean computed. Results: The average age of the 36 patients was 66 ± 29 years. Photographs were taken 32 ± 16 months after exenteration. Across all photographs, the averages score given by the first observer (4.3 ± 2.2) and second observer (3.4 ± 1.5) were similar (t = –1.9; p = 0.07). From the Bland-Altman plot, the mean difference in score (0.8 ± 1.8) was close to zero, with 95% confidence limits for agreement are indicated by the dashed lines and spanning from −2.6 to 4.3. Conclusion: MOEWAT can be successfully used to stage wound healing in exenterated sockets, with good inter-observer agreement.